Pelindung Dinding Terhadap Hujan Asam Menggunakan Geopolimer Berbasis Nanosilika dan Cellulose Nanocrystals - Cut Rahmawati (Kadiri University, 2023)
Geopolymers have a weakness in durability against exposure to acid rain. Nano-silica and Cellulose Nanocrystals (CNCs) can be incorporated to enhance the acid rain resistance of geopolymers. This study aims to investigate the durability of geopolymer-based nano-silica and CNCs against exposure to acid rain. This study employed a rain simulation infiltration method. The concentrations of nano-silica and CNCs used were 4% and 1%, respectively. The compressive strength of the geopolymer specimens was tested before and after exposure to assess the effects of acid rain. Additionally, SEM and XRD tests were conducted to analyze microstructural changes. The results revealed a significant reduction in the compressive strength of the geopolymer without nano silica and CNCs (36.14% and 26.73% at pH 4 and 5, respectively). In contrast, the geopolymer paste containing nano-silica and CNCs exhibited lower reductions of 22.93% and 19.77% at pH 4 and 5, respectively. These findings indicate that the addition of nano-silica and CNCs contributes to the preservation of compressive strength. The observed effect is attributed to the ability of nano-silica and CNCs to impede acid attack on the geopolymer paste, thereby preventing the degradation of calcium levels present in the fly ash within the geopolymer. The strength degradation of the geopolymer paste resulted from the breakdown of Al–O, Si–O, and calcium bonds within the system, triggered by the reaction with H2SO4 from the acid rain. Nano-silica and CNCs-based geopolymers exhibit positive effects and can be utilized as a coating on the walls of buildings.